Polyuretany využívané v technologii tváření - Špičák, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Práce vypracovaná v rámci bakalářského studia předkládá rešerši na téma: „Polyuretany využívané v technologii tváření“. Skládá se z jejich přehledu, vlastností a dále rozebírá jednotlivé metody tváření, které využívají polyuretany jako elastické nástroje.

The work carried out within the framework of Bachelor's study presents the exploration of the facts on the theme: „Polyurethanes in forming technology. It consists of the schedule, characteristics and in other part analyzes different methods of the forming which use a polyurethanes as an elastic instrument.
Polyurethanes in forming technology
Keywords: polyuretan; tváření; stříhání; ohýbání; tažení; polyurethane; forming; cutting; bending; drawing